Testosterone Reduces Knee Passive Range of Motion and Expression of Relaxin Receptor Isoforms via 5α-Dihydrotestosterone and Androgen Receptor Binding - Dehghan, F.; Muniandy, S.; Yusof, A.; Salleh, N. (MDPI, 2014)
Ovarian steroids such as estrogen and progesterone have been reported to influence knee laxity. The effect of testosterone, however, remains unknown. This study investigated the effect of testosterone on the knee range of motion (ROM) and the molecular mechanisms that might involve changes in the expression of relaxin receptor isoforms, Rxfp1 and Rxfp2 in the patella tendon and lateral collateral ligament of the female rat knee. Ovariectomized adult female Wistar rats received three days treatment with peanut oil (control), testosterone (125 and 250 μg/kg) and testosterone (125 and 250 μg/kg) plus flutamide, an androgen receptor blocker or finasteride, a 5α-reductase inhibitor. Duplicate groups received similar treatment however in the presence of relaxin (25 ng/kg). A day after the last drug injection, knee passive ROM was measured by using a digital miniature goniometer. Both tendon and ligament were harvested and then analysed for protein and mRNA expression for Rxfp1 and Rxfp2 respectively. Knee passive ROM, Rxfp1 and Rxfp2 expression were significantly reduced following treatment with testosterone. Flutamide or finasteride administration antagonized the testosterone effect. Concomitant administration of testosterone and relaxin did not result in a significant change in knee ROM as compared to testosterone only treatment; however this was significantly increased following flutamide or finasteride addition. Testosterone effect on knee passive ROM is likely mediated via dihydro-testosterone (DHT), and involves downregulation of Rxfp1 and Rxfp2 expression, which may provide the mechanism underlying testosterone-induced decrease in female knee laxity.